GENDER EQUALITY IN THE FIELD OF RESEARCH AND INNOVATION - EU VERSUS SERBIA, NORTH MACEDONIA AND MONTENEGRO - Todorović Lazić, Jelena (Serbian political thought, 2023)
During the last decades, the EU has particularly focused on establishing equal opportunities and equal treatment of women and men in all spheres of life. Regulatory measures that the Union gradually introduced in the area of gender equality, such as: measures that ensure equal pay, maternity protection, regulations on parental leave, contributed to this. The She Figures publication, published by the European Commission every three years, uses the latest available statistics to monitor the state of gender equality in the field of research and innovation, thus providing us with the opportunity to parallelize data and analysis for 88 indicators across Europe. This is also the subject of this paper. One of the goals is to determine the extent to which the gender equality policy in the field of research and innovation is integrated in the associated countries: Serbia, North Macedonia and Montenegro, i.e., to what extent the data related to these three countries match or deviate from the average at the EU level based on the data provided by the aforementioned publication, 2021 edition. According to some indicators discussed in this Report, the situation is much better in these countries compared to the European average (number of women graduating from doctoral studies, total number of female researchers, number of female researchers employed in the main sectors of the economy). Also, for two important chapters we lack data for these three countries, so we cannot draw more comprehensive conclusions other than that these countries have largely included gender equality in their policies in the field of research and innovation and that in some categories they have even better results in favor of women than is the case in more developed countries of the European Union.